(INTELLEGENCE QUOTIENT) ANAK USIA SEKOLAH DASAR : A LITERATUR REVIEW - Hilman Mulyana; Fitriani Mardiana Hidayat; Risda Hidayanti (JURNAL KESEHATAN INDRA HUSADA, 2021)
Stunting is a nutritional problem in the world or globally that has an impact on children's growth and development, one of which is the intellectual intelligence of children, which affects the level of intelligence possessed by children and can cause a decrease in the level of productivity in the future. This review literature study aims to see and analyze the impact of stunting on intellectual intelligence (Intelligence Quotient) of elementary school-age children. Keywords: Stunting, intellectual intelligence, school-age children. The method used in this research is a literature review taken from national and international journals related to stunting and intellectual intelligence. Sources of searching for journals through several databases, namely Google Scholar, Pubmed, Science Direct, and IJSR within a period of 10 years (2010 to 2020), obtained search results for 15 journals that were reviewed. The results of research from 15 journals, 12 journals showed the impact of stunting on children's intellectual intelligence after elementary school and 3 journals showed no impact on the intellectual intelligence of elementary school-aged children. The conclusion of the researchers found that nutritional status and stunting have a relationship with cognitive development and intellectual intelligence (IQ) of elementary school-age children, and stunting has a negative impact on children's intellectual intelligence, children's cognitive development, and student learning achievement. Suggestions in this study are that families can fulfill and improve nutrition in children to prevent malnutrition and stunting, conduct consultations with nurses regarding monitoring growth and development in children so as to achieve optimal growth and development.